Tfh and Tfr cells - Graca, Luis (Henry Stewart Talks, 2021)
T follicular helper (Tfh) cells, T-dependent and T-independent B cell pathways, Tfh: B cell interactions lead to the emergence of germinal centers, Affinity maturation, T follicular regulatory (Tfr) cells are key regulators of the germinal center response